Marketing Communications and Promotion Strategies for Entrepreneurs - Nalom Siagian; Suwardi Lubis; Erlina Erlina; Ritha F Dalimunthe (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Entrepreneurs assemble and unite all the necessary resources i.e. money, people, business models, strategies and the ability to take risks to turn new inventions into a workable business. A business refers to a marketing mix consisting of product, price, place and promotion. As a marketing mix, promotion has several challenges to the effectiveness and efficiency of the marketing message to be conveyed. For this reason, the concept of integrated marketing communication emerged which combines several marketing communication tactics into an integrated manner to increase the effectiveness and efficiency of marketing messages. Knowledge, understanding and implementation of integrated marketing communications will help an entrepreneur to help market his brand. This paper aims to conduct a theoretical study between entrepreneurship and integrated marketing communication as a method of marketing promotion. If carried out comprehensively, integrated marketing communications will help an entrepreneur to help him introduce, form a positive impression and retain his customers for his brand.